Germ cell tumor: A seven-year experience Children Welfare Teaching Hospital: Germ cell tumor; 7 years’ experience Children Welfare Teaching Hospital - alsaeed, raghad majid; Jassim, Afrah M.; Razaq, Samaher A.; AL-Jadiry, Mazin F. (Journal of the Faculty of Medicine Baghdad, 2021)
Background: Germ cell tumors are a rare heterogeneous group of cancers with high cure rates in the pediatric age group.Objectives: To study the clinical and pathological features in a group of patients with germ cell tumors and to evaluate their outcomes.Patients and methods: A record review was undertaken on a group of patients with germ cell tumor who were admitted to the Children Welfare Teaching Hospital in Baghdad during the years 2009 - 2015. Information on gender, age, clinical signs, pathological findings, treatment and overall survival rate were reviewed.Results: The patients had a mean age of 4.2 years (ranging from 1 month - 14 years). There were 45 girls and 16 boys. Abdominal pain was the most common presentation in 17 patients followed by a lower back mass in 16 patients. Primary sites included extra gonadal (sacrococcygeal 18, pelvis 5, vagina 4, gluteal 3, intra-cardiac, and one each for the mediastinum, orbit and rectum), and gonadal (18 ovarian and 9 testicular). After a mean period of follow-up of 42 months, the overall survival at 1 year was 59%.Conclusion: The prognosis of children with germ cell tumors is favorable, regardless the site and histopathology.